Unveiling the influence of pH on the crystallization of hybrid perovskites, felivering low voltage loss photovoltaics - Noel, N; Congiu, M; Ramadan, A; Fearn, S; McMeekin, D; Patel, J; Johnston, M; Wenger, B; Snaith, H (Cell Press, 2017)
Impressive power conversion efficiencies coupled with the relative ease of fabrication have made perovskite solar cells a front runner for next-generation photovoltaics. Although perovskite films and optoelectronic devices have been widely studied, relatively little is known about the chemistry of the precursor solutions. Here, we present a study on the hydrolysis of N,N-dimethylformamide, correlating how pH changes related to its degradation affect the crystallization of MAPbI3xClx perovskite films. By careful manipulation of the pH, and the resulting colloid distribution in precursor solutions, we fabricate perovskite films with greatly improved crystallinity, which when incorporated into photovoltaic devices reproducibly yield efficiencies of over 18%. Extending this method to the mixed cation, mixed halide perovskite FA0.83MA0.17Pb(I0.83Br0.17)3, we obtain power conversion efficiencies of up to 19.9% and open-circuit voltages of 1.21 V for a material with a bandgap of 1.57 eV, achieving the lowest yet reported loss in potential from bandgap to a VOC of only 360 mV.